DAYA SAING KOMODITAS KUNYIT INDONESIA DI PASAR INTERNASIONAL MENGGUNAKAN PENDEKATAN RCA DAN EPD - Zainal Abidin; Ni Desak Gede Putri Megagita; Ktut Murniati (Journal of Food System & Agribusiness, 2021)
Turmeric has been known as one of Indonesia’s prospective commodity for years. It has great value for food, medicine, and pharmaceutical purposes.  The turmeric production of Indonesia from 2008 to 2019 was tent to increase since the harvested area for turmeric has been extended. This progress indicates that Indonesia’s turmeric may has a great chance to developed. This research aimed to measure the competitiveness of Indonesia’s turmeric in the international market. Competitiveness analysis employs the Revealed Comparative Advatage (RCA) and Export Product Dynamic (EPD). The study suggests that that Indonesia’s turmeric commodity is highly competitive in global market using RCA analysis. Using EPD calculation, Indonesia export on turmeric accid is in falling star position.